PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PADA MATERI BILANGAN BULAT - Tiroida Harahap; Agus Makmur; Wirna Arifitriana (JURNAL MathEdu (Mathematic Education Journal), 2022)
Research shows that the results of the student's math problem solving skills test by applying the Cooperative Type Think-Pair-Share learning model in cycle I obtained a percentage of 70% with the criterion "Good Enough" and in cycle II earned a percentage of 80%% a "Good". % Based on the results of observation of student activity in cycle I obtained a student activity level of 70.56% with the category "Enough" and in cycle II student activity amounted to 86.68% with the category "Good". As for the results of observation of teacher ability in cycle I obtained an average score of 3.35with the category of assessment " Good Enough" and in cycle II obtained an average score of 3.85 with a "Good" assessment categor.